Stopień pasywizacji tekstów prawniczych w oryginale i w przekładzie. Analiza kontrastywna angielsko-francusko-polska - Stawecka-Kotuła, Agnieszka (Acta Neophilologica, 2020)
The main focus of this paper is the degree of passivisation in English, French and Polish legal texts, considered as fully representative of specialised discourse, examined in selected original and translated texts. Since it is assumed that typological differences between languages determine users’ choices regarding their selection of passive structures, the very same tendencies should be also reflected in the specialised, legal variant of the language. The aim of this study is to verify this assumption by juxtaposing the research findings from two specialised corpora, namely a comparable corpus and a parallel corpus, both created by the author following corpus linguistics principles.